Antibacterial activities of endophytic fungi from leaves of Cassia alata L. (Candle Bush). - Palmares, Flordeliza P.
Medicinal plants have been in use for centuries that relies on the direct use of these plants as raw materials thus posing a risk of overexploitation leading to resource depletion. This situation led to the pursuit of other less destructive alternatives for depriving the same benefits from these plant. Among such alternative is to search for bioactive compounds from fungal endophytes. Fungal endophytes are species found occurring inside host plants but do not cause any damage to living plant. Thus, for the last decade there was a growing interest on these fungi with various aspects of their ecology and potential applications. The Philippines is also gifted with numerous medicinal plants but so far not may have been studied for the occurrence of fungal endophytes. Cassia alata is used widely for its antifungal property and this study aims to provide additional information on the occurrence of fungal endophytes on this plant. This study generally aimed to enumerate the various fungal endophytes from leaves of Cassia alata. Specifically, it aimed 1). isolate, characterize and identify species of endophytic fungi, 2)describe population of fungal endophytes in terms of species composition, frequency of occurrence and colonization frequency, 3) evaluate the antimicrobial activity of their endophytic fungi against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Salmonella sp. Leaves were collected from Cassia alata and were processed within 24 hours. Leaf discs were obtained and were surface sterilized before inoculating them in Potato Dextrose Agar (PDA) plates with Streptomycin-Penicillin antibiotic. Plates were incubated at room temperature for 2-3 weeks and observed for fungal growth on a daily basis. Fungi were identified based on available keys and monographs. Seventy-two (72) endophytic fungal isolates belonging to 19 species were collected from 100 leaf segments (20 leaf samples). In general, Aspergillus was the most dominant genera seen. Aspergillus flavus (15 percent) and Aspergillus niger (10 percent) were the very frequently collected species. The frequently occuring species Aspergillus fumigatus (11 percent), Penicillium citrinum (7 percent) and Sclerotum cf. sp. (6 percent). Three species with highest frequency of occurrence- A. flavus, A. niger and A. fumigatus - were assessed for their antimicrobial activity against Escherichia coli, Staphylococcus aureus, bacillus subtilis, and Salmonella sp. by disc diffusion method and zone of inhibition were measured to determine antibacterial acitvity. Among the three isolates tested, A. fumigatus and A. flavus exhibited antibacterial activity against 3 out of 4 of the test bacteria, showing broad spectrum of activity. A. niger failed to inhibit any of the bacteria. The isolation of endophytic fungi in the present study indicates their richness of diversity in Cassia alata and antibacterial analysis may provide additional sources of antibacterial compounds.